THE ROLE OF PROVERBS IN TEACHING ENGLISH - Таджиева, Мастура (Журнал иностранных языков и лингвистики, 2021)
This paper deals with using proverbs in teaching and learning English and how teachers can make use of proverbs to teach language materials and to keep the students interested in learning English. Basically, proverbs reflect human experience across cultures and languages, which contain folk wisdom tested throughout the time. Introducing a foreign culture and values can be carried out through the use of proverbs. Teachers can use different vocabulary activities through proverbs in teaching process.